Determinants of Toxic Behavior Among Mobile Legends Players: Evidence from Players in Indonesia - Heaven Khen Helio Sentragyo; Lianto Lianto (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2026)
Toxic behavior remains a persistent concern in competitive online gaming, yet its psychological determinants have received limited empirical attention in Southeast Asian contexts. This study examines the factors influencing toxic behavior among Mobile Legends: Bang Bang players in Indonesia by replicating an integrated framework comprising attitude toward toxic behavior, toxic behavior victimization, behavioral control, and toxic disinhibition. Data was collected through an online self-administered questionnaire between May and June 2026 from active players with experience in competitive team-based matches and in-game communication. The proposed relationships were analyzed using partial least squares structural equation modeling. The results indicate that attitude toward toxic behavior and toxic behavior victimization positively influence toxic disinhibition, whereas behavioral control negatively influences both toxic disinhibition and toxic behavior. Toxic disinhibition is the strongest predictor of toxic behavior. However, attitude toward toxic behavior has no significant direct effect on toxic behavior, suggesting that favorable attitudes toward toxicity are translated into actual behavior primarily through reduced psychological restraint. Toxic disinhibition also significantly mediates the effects of attitude, victimization, and behavioral control on toxic behavior. The model explains 50.8% of the variance in toxic behavior. These findings extend the applicability of the integrated toxic behavior framework to the Indonesian mobile gaming context and suggest that interventions should strengthen players’ self-regulation, reduce the normalization of toxic interactions, and promote respectful communication within gaming communities.